INDEPENDENSI OTORITAS LEMBAGA MASYARAKAT ADAT MARIND, DEFORESTASI DAN OTORITARIANISME AGRARIA DI KABUPATEN MERAUKE - Wea, Donatus; Sarang, Rikardus Kristian; Mite, Elyas (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
This study explores the relationship between large-scale agrarian development, the rate of deforestation, and the independence of the Marind Indigenous People’s Institution (Lembaga Masyarakat Adat/LMA) in Merauke Regency. A descriptive qualitative approach was employed. Data were collected through in-depth interviews with ten informants, including representatives of the LMA, affected communities, local government officials, and investors, and were analyzed using the Miles, Huberman, and Saldana model. The findings reveal that large-scale agrarian projects, developed within the framework of the Food Estate Program and Plantation Investments, have significantly contributed to forest conversion and the weakening of Marind customary authority. These projects have not only caused the physical loss of forests but also the loss of the Marind people’s living space and their spiritual relationship with nature. Forests, which for centuries have constituted the core of their identity and livelihood, have now been transformed into economic assets governed by the logic of capital and state bureaucracy. Consequently, deforestation should not be understood merely as an environmental phenomenon but as a cultural and political crisis reflecting the fragility of mechanisms protecting indigenous rights. The Marind LMA often faces marginalization in land release processes, while local communities receive disproportionate compensation. This study recommends agrarian policy reforms that prioritize indigenous and environmental interests, the strengthening of customary institutional capacities, and the integration of local wisdom into land governance.